The Education versus Training and the Skills versus Competency debate - T. Gibbs; D. Brigden; D. Hellenberg (South African Family Practice)
The essence of modern medical education lies in the ability of defining and developing its terminology, which all too often is used in a less than thoughtful and inappropriate manner. Educationalists place emphasis upon the concept of learning rather than teaching; learning which is specifically student centred and student directed learning rather than teacher centred didactic teaching. However within this change environment we still prefer to use the word training, as in vocational training, to describe a specific programme and aspire to levels of competency that hopefully match the learning outcomes of the programme. This article opens the debate on whether the satisfactory completion of a learning programme is sufficient (cf completion of vocational training) or whether we should be assessing the learner through levels of defined competency relevant to their professional career.